Efficacy, safety and tolerability of linezolid for the treatment of XDR-TB: a study in China. Issue 5 (May 2016) - Berry, Catherine; Yates, Tom A.; Seddon, James A.; Phillips, Patrick P. J.; du Cros, Philipp
Heterogeneity amongst cohorts of patients treated for drug-resistant tuberculosis (TB) make assessing the efficacy of new drugs and regimens unreliable without randomisation [1]. We warmly welcome the randomised controlled trial (RCT) "Efficacy, safety and tolerability of linezolid for the treatment of XDR-TB: a study in China" presented by Tang et al . [2]. Linezolid is now included on the WHO list of essential medicines [3] and falling prices will improve access. That Tang et al . [2] report a 35.3% absolute reduction in the risk of a poor outcome by adding linezolid to an optimised background regimen argues in favour of wider use. Linezolid remains a WHO "Group 5" drug, classifying it as an "anti-TB drug with limited data on efficacy and/or long term safety in the treatment of [drug-resistant]-TB" [4]. The limited data on the efficacy of drugs in this class has recently been reviewed [5]. These WHO classifications may shortly be revised and the exciting results from this study have the potential to alter guidance regarding the treatment of extensively drug-resistant (XDR) TB. We note the proposal to re-classify linezolid into Group 3 in an editorial in the October edition of the European Respiratory Journal [6]. It is with this in mind that we seek some clarifications. Response to the interesting RCT on linezolid for XDR-TB and request for information which may impact new guidelines http://ow.ly/Z1dX5